A Girl with Hip Swelling and Convulsion - Miah, Md Titu; Ayaz, Khan Fariduddin Mohammad; Begum, Aysha; Azad, Khan Abul Kalam; Mowla, Syed Ghulam Mogni (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2017; 35(2): 100